1981
DOI: 10.1111/j.1365-2672.1981.tb00917.x
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli Content of Mytilus edulis from Analysis of Whole Tissue or Digestive Tract

Abstract: The dissected digestive tract of edible mussels from two sites was examined for Escherichia coli and the counts compared with those from the total tissue of parallel mussel samples. The method using 4 x 1 ml pour plates was preferred to the 1 x 4 ml pour plate or to the 2 x 0.2 ml spread plates. Counts from the digestive tract were up to sixfold higher than parallel counts using total tissue. Digestive tract inoculum also produced amplified Esch. coli detection when lightly polluted mussels were examined by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Cold weather as well as availability of organic matter are playing major roles in survival and presence of heterotrophic bacteria [7]. Furthermore, total coliforms is considered as an indicator for long-term water pollution [1]. The present study showed that the total coliforms were different according to sites of collection and the highest number was recorded in July which was almost 1023/100 ml ( Table 6).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Cold weather as well as availability of organic matter are playing major roles in survival and presence of heterotrophic bacteria [7]. Furthermore, total coliforms is considered as an indicator for long-term water pollution [1]. The present study showed that the total coliforms were different according to sites of collection and the highest number was recorded in July which was almost 1023/100 ml ( Table 6).…”
Section: Discussionmentioning
confidence: 57%
“…This situation will increase the risk of water pollution as the rainfalls will clean out all pollutants towards the rivers. This is one of the major causes of increased numbers and types of bacterial indicators in water bodies [1,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work with mussels from the West Pier and Mumbles sites (Al-Jebouri & Trollope, 1978 ;Al-Jebouri, 1980) showed the presence in these samples of Shigella dysenteriae, Yersiniaenterocolitica, Klebsiellapneumoniae, Enterobacter cloacae and Serratia sp . There are outfalls discharging sewage effluents near these shore sites and mussel samples from Mumbles which were the subject of a recent report by us on E. coli content (Al-Jebouri & Trollope, 1981), concurrently yielded the food poisoning organism Salmonella hadar (unpubl . results) .…”
Section: Discussionmentioning
confidence: 99%